Detecting Experience Debt in Internal IT Services: A Minimal Touchpoint-Based XLA for Small EdTech Startups - Marcel; Tubagus Ahmad Marzuqi (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
Small EdTech startups often use SLA numbers to check whether internal IT services are working well. The problem is that these numbers usually show only whether the service was restored and how long it took. They do not show what users actually experienced while the problem was happening. This study looks at that hidden part. It uses the idea of experience debt to describe small but repeated service problems that slowly make daily work harder. The study was conducted in three small EdTech startups in Jakarta. It used survey data and interview data collected in the same period. The survey produced 274 valid responses across six touchpoints and five experience dimensions. The interviews involved 18 informants and focused on the service moments they remembered as most difficult. The weakest point appeared at TP2, where users faced access problems and often felt confused about what was happening, what to do next, and whether the issue was really finished. At TP4 and TP5, the main problem was fairness. Users often felt stuck in a process they could not see, had to repeat the same explanation, or did not know who was handling their request. From these findings, the study developed a simple touchpoint-based XLA as a one-page review tool. Its purpose is to help small teams notice user experience problems that normal SLA monitoring often misses. More research is still needed in other service settings and organisations.